1993
DOI: 10.1038/ki.1993.346
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of monocyte chemoattractant protein-1 in anti-thymocyte antibody-induced glomerulonephritis

Abstract: The infiltration of monocytes-macrophages in the glomerulus is one of the hallmarks of glomerulonephritis and may play an important pathogenetic role. Monocyte chemoattractant protein-1 (MCP-1) and colony stimulating factor-1 (CSF-1) are monocyte-specific cytokines with chemoattractant and activating activities for monocytes. MCP-1 and CSF-1 can be generated by several cell types, including glomerular mesangial cells, and can be stimulated by cytokines and immune complexes. To study the expression of CSF-1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
63
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(67 citation statements)
references
References 39 publications
4
63
0
Order By: Relevance
“…MCP-1 is released from many types of cells, including macrophages, lymphocytes, platelets, fibroblasts, endothelial cells, epithelial cells, 42 and mesangial cells. 43 The MCP-1 mRNA level in the glomeruli of the pCAGGS-vIL-10 rats was significantly lower than that in the glomeruli of the pCAGGS rats on day 4 after injection but not on day 7, despite the reduction in the number of macrophages in the glomeruli. These results suggested that vIL-10 could prevent glomerular macrophage accumulation, but it was not able to prevent the production of MCP-1 by macrophages and other cells by day 7.…”
Section: Discussionmentioning
confidence: 83%
“…MCP-1 is released from many types of cells, including macrophages, lymphocytes, platelets, fibroblasts, endothelial cells, epithelial cells, 42 and mesangial cells. 43 The MCP-1 mRNA level in the glomeruli of the pCAGGS-vIL-10 rats was significantly lower than that in the glomeruli of the pCAGGS rats on day 4 after injection but not on day 7, despite the reduction in the number of macrophages in the glomeruli. These results suggested that vIL-10 could prevent glomerular macrophage accumulation, but it was not able to prevent the production of MCP-1 by macrophages and other cells by day 7.…”
Section: Discussionmentioning
confidence: 83%
“…Several studies show that MCP-1 plays a predominant role in the initiation and progression of various forms of nephritis (7,14,15). In experimental models of crescentic nephritis and antiglomerular basement membrane nephritis, treatment with neutralizing anti-MCP-1 Abs or antagonistic MCP-1 muteins prevented proteinuria and formation of lesions, reduced infiltration of mononuclear cells and T lymphocytes, and reduced sclerosis by lowering collagen and matrix production (16,17).…”
mentioning
confidence: 99%
“…In the kidney, MCP-1 expression was enhanced in different animal models of experimental glomerular nephritis (e.g. [6][7][8][9]). Glomerular MCP-1 was also detectable in biopsies from patients with inflammatory or proliferative glomerulonephritis [9].…”
Section: Introductionmentioning
confidence: 99%
“…In the model of anti-thymocyte antibody-induced glomerulonephritis [6], MCP-I was found to be enhanced in an early phase, which might relate to the effect of immune complexes, but it was also elevated at a later time period, when both PDGF and interleukin-1 (IL-1) levels were known to be increased.…”
Section: Introductionmentioning
confidence: 99%